Kepemimpinan Kepala Sekolah dalam Pengembangan Iklim Organisasi dan Kerja Guru - Zainal Fauzi (Transformatif, 2017)
The low quality of education is one of the many national issues in education today. This issue is caused by various factors, one of which is a factor of school leadership. The headmaster as one of the human resources have an important role in the school. the effectiveness of decision-making and policy will determine how the behavior of school leadership. Based on the results of data processing and analysis concluded that (1) there is a significant relationship between the behavior of school leadership and job satisfaction; (2) there is a relationship between organizational climate and job satisfaction; (3) together there is a relationship between the behavior of school leadership and organizational climate and job satisfaction. Based on the results of the study, presented suggestions to the principal in order to improve its ability to plan tasks and assign work procedures but it also can establish good relationships, being warm and appreciate and trust of its members. The school principal is also expected to create a school climate that is as good as their communication, planning, work procedures, and achieving good results.Keywords: leadership behavior, organizational climate, job satisfaction, teacher